Hubungan Kecemasan Ibu Dengan Kesediaan Melakukan Imunisasi DPT Combo DI Wilayah Kerja Puskesmas Pembantu Ranuwurung Lumajang - Musarofah, Musarofah; Sunanto, Sunanto; Hidayati, Tutik (NHM PRESS, 2023)
Combination immunization multivalent diphtheria, pertussis, and tetanus (DPT) combination immunization is the basis of many childhood programs around the world. maintaining the acceptance and absorption of the DPT combination vaccine is paramount, given its benefits in protecting against various diseases in the community. This study aims to to identify the relationship between maternal anxiety and willingness to do DPT Combo at Ranuwurung Health Center, Lumajang. Research design using correlation with cross sectional approach. The population of this study consisted of 58 mothers with young children who were to participate in the DPT Combo at the Ranuwurung Health Center in Lumajang. Simple Random Sampling is the method of sampling that is employed. Data were collected using a state anxiety inventory (STAI) questionnaire and willingness to receive vaccines. data analysis using Predictive Analytics SoftWare Version 18 with the spearman rho test at a significance level of <0.05. The results showed that more than half (56.9%) of mothers with children who were to be immunized with DPT had moderate levels of anxiety and almost half (43.1%) had a willingness to do well. the results of statistical analysis showed that anxiety significantly indicated the willingness to do the DPT Combo exercise at a moderate correlation level (p-value = 0.001; r = 0.438). Continued education, health promotion, and encouragement to help families comprehend are suggested. Families where the mother and child reside ultimately voluntarily accept the DPT combination immunization